Additively manufactured (3DP) thermite structures vs conventionally manufactured equivalents - McGee, Christine; Vrcelj, Ranko (IPSUSA Seminars, 2022)
Research into additive manufacturing (AM) has been steadily expanding over the past five decades. Where once only polymeric materials could be reliably printed, AM has been adapted to print with a range of materials such as biological, metallic, ceramic and even foodstuffs. The advantages of manufacturing in an additive manner include; a) a layer-by-layer approach allows the creation of architecturally complex structures, b) a reduction in weight, c) lessening of waste and d) the ability to create parts that that are otherwise difficult or too costly to produce. Pyrotechnic materials, including thermites, are used in a wide range of commercial and defence applications. However, hazards present during manufacturing and storage have resulted in major accidents around the world, with subsequent loss of life and in some cases loss of public infrastructure. AM, using a dry powder printing technique means that parts can be manufactured on demand, reducing the need for storage of large volumes of fully formed products or mixes, thus increasing the safety over lifetime of a product. The performance of pyrotechnics materials is dependent on a number of properties, including chemical composition, thermodynamic properties and physical form. In combination with composition, architecture could be utilised to understand and control these properties. A bespoke printer capable of additively manufacturing pyrotechnic materials has been constructed with the aim to explore this research area. In this presentation, we compare the burn rates of AM thermites and compare them to conventionally fabricated compositions and discuss the effects of the print parameters and confinement. We conclude with the results from the burning of AM thermite structures and compare their performance with conventionally prepared equivalent thermite examples.